2020
DOI: 10.17645/pag.v8i1.2510
|View full text |Cite
|
Sign up to set email alerts
|

Electoral Behaviour in a European Union under Stress

Abstract: Is electoral behaviour affected by the current challenges of the EU and, if it is, through which channels and mechanisms? This study offers a cross-national analysis together with a broad understanding of both the crisis phenomenon and electoral behaviour. To investigate this research question appropriately, we first distinguish at the most general level between the two main behavioural alternatives at play when it comes to electoral behaviour, namely abstention and vote choice. Second, and no less important, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Transparency is frequently regarded as one of the fundamental principles that should be upheld by electoral management bodies (EMBs), where officials lay out their objectives, responsibilities, and limitations. They also provide information about citizens' rights and voting procedures, engage with stakeholders frequently, and provide justifications for As for some previous research on the electoral process, one of them is from Braun and Tausendpfund whose discoveries help comprehend the multi-level democracy better (Braun & Tausendpfund, 2020). Besides, Jereoma suggested that the National Electoral Commission be independent and should employ its own legal counsel to supervise election-related legal issues, including the inclusion of electoral offenses as felonies under the various state laws (Jereoma, 2022).…”
Section: Mapping Of Model Management Elections Issuesmentioning
confidence: 99%
“…Transparency is frequently regarded as one of the fundamental principles that should be upheld by electoral management bodies (EMBs), where officials lay out their objectives, responsibilities, and limitations. They also provide information about citizens' rights and voting procedures, engage with stakeholders frequently, and provide justifications for As for some previous research on the electoral process, one of them is from Braun and Tausendpfund whose discoveries help comprehend the multi-level democracy better (Braun & Tausendpfund, 2020). Besides, Jereoma suggested that the National Electoral Commission be independent and should employ its own legal counsel to supervise election-related legal issues, including the inclusion of electoral offenses as felonies under the various state laws (Jereoma, 2022).…”
Section: Mapping Of Model Management Elections Issuesmentioning
confidence: 99%
“…Through the structural approach, we were able to assign a differentiated weighting to the vectors of political intervention, combining this reality with citizens' perception of the local government's achievements. This model allows us to observe the levels and nature of the collective perception in relation to the public behavior of elected officials from a quantifiable, comparable, and predictive perspective of future electoral behavior (Braun and Tausendpfund 2020;Tavokin 1996).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This was particularly the case in numerous countries that experienced economic hardship following the sovereign debt crisis and austerity politics in Europe. The ‘Euro crisis’ yielded severe political repercussions in elections all over Europe (Hernández and Kriesi, 2016) and already affected the previous European elections in 2014 (Braun and Tausendpfund, 2020; Hobolt and De Vries, 2016). The fact that the economy is a primary concern for many voters is certainly not a new insight, as the economic voting literature illustrates (Lewis-Beck and Stegmaier, 2000).…”
Section: Policy Issues and European Electionsmentioning
confidence: 99%